SPARC from Olfactory Ensheathing Cells Stimulates Schwann Cells to Promote Neurite Outgrowth and Enhances Spinal Cord Repair - Au, Edmund (J Neurosci, 2007)
Olfactory ensheathing cells (OECs) transplanted into the lesioned CNS can stimulate reportedly different degrees of regeneration, remyelination, and functional recovery, but little is known about the mechanisms OECs may use to stimulate endogenous repair. Here, we used a functional proteomic approach, isotope-coded affinity tagging and mass spectrometry, to identify active components of the OEC secreteome that differentially stimulate outgrowth. SPARC (secreted protein acidic rich in cysteine) (osteonectin) was identified as an OEC-derived matricellular protein that can indirectly enhance the ability of Schwann cells to stimulate dorsal root ganglion outgrowth in vitro. SPARC stimulates Schwann cell-mediated outgrowth by cooperative signal with laminin-1 and transforming growth factor β. Furthermore, when SPARC-null OECs were transplanted into lesioned rat spinal cord, the absence of OEC-secreted SPARC results in an attenuation of outgrowth of specific subsets of sensory and supraspinal axons and changes the pattern of macrophage infiltration in response to the transplanted cells. These data provide the first evidence for a role for SPARC in modulating different aspects of CNS repair and indicate that SPARC can change the activation state of endogenous Schwann cells, resulting in the promotion of outgrowth in vitro, and in vivo.